Constructing research questions : doing interesting research - Alvesson, Mats, 1956-; Sandberg, Jo?rgen (Los Angeles, California : SAGE, 2013)
All researchers want to produce interesting and influential theories. A key step in all theory development is formulating innovative research questions that will result in interesting and significant research. Traditional textbooks on research methods tend to ignore, or gloss over, actual ways of constructing research questions. In this text, Alvesson and Sandberg develop a methodology for identifying and challenging assumptions underlying existing theories and generating research questions, using examples from across the social sciences.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology